The clinical effectiveness of adhesive agents in posterior restorations: Which adhesive strategy performs better? - Naji Ziad Arandi; Mohammad Thabet (Wolters Kluwer Medknow Publications, 2021)
The clinical effectiveness of adhesive agents has been mainly evaluated using class V restorations. Clinical studies evaluating adhesives in combination with posterior composites are scarce and of short-term periods. This paper is aimed to review the current literature on the clinical effectiveness of contemporary adhesives when used to restore posterior teeth (Class I and Class II). To conduct this review, Scopus, PubMed, and Google Scholar databases were used to search for peer-reviewed articles on the clinical performance of adhesive agents in posterior composite restorations. Search terms used included "adhesive agents," "clinical evaluation," "composite restorations," "posterior teeth," "self-etch adhesives," "etch -and -rinse adhesives," and "universal adhesives." To enrich the results, reference mining of the articles that were identified was used to locate other papers. The process of cross-referencing continued until no new articles were identified. No limits were placed on the year of publication, but only articles in English were considered. The current review found that simplification in the adhesive technique so far seems to affect the clinical performance. There is a relative paucity of evidence relating to the performance of universal adhesive agents in posterior restorations. Further long-term clinical studies are needed to evaluate the clinical performance of adhesive agents.